Bayan ko (GMA News TV's original series, 2013)
"It tells the story of newly elected Mayor Joseph Santiago who sets out to make a difference in his hometown. Shot entirely on high-definition, this groundbreaking, six-part drama is the first of its kind on Philippines television, tackling issues such as corruption, bureaucracy, malnutrition, illegal logging and political dynasties."--Container